Composite current collector and preparation method of battery cell comprising composite current collector

By providing a protective layer composed of polymer material, metal oxide and conductive agent on both sides of the aluminum foil layer of the battery cell, a composite liquid collector is formed, which solves the problems of short circuit and thermal runaway during external force failure, and improves the safety and performance of the battery cell.

CN119852422AActive Publication Date: 2025-04-18东莞维科电池有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510023027.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-18
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

When the battery cell is damaged by external forces, the existing current collector lacks effective protection, resulting in direct contact between the negative electrode graphite and the aluminum foil, causing short circuits and thermal runaway, increasing safety risks.

Method used

A composite fluid collector is used, including an aluminum foil layer and a protective layer disposed on both sides in the thickness direction of the aluminum foil layer. The protective layer consists of a polymer material, a metal oxide and a conductive agent. The conductive agent can be SP, CNT, graphene or Kochen black, etc., and is composited on the aluminum foil layer by lamination to form a composite fluid collection.

Benefits of technology

By adding a protective layer, the possibility of the negative electrode graphite contacting the aluminum foil is significantly reduced, the risk of short circuit is reduced, the safety and reliability of the battery cell is improved, and the charge and discharge performance and service life are optimized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852422A_ABST
    Figure CN119852422A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and mainly relates to a composite current collector which comprises an aluminum foil layer and protective layers arranged on the two sides of the aluminum foil layer in the thickness direction. The protective layer comprises a polymer material, a metal oxide and a conductive agent, and the conductive agent is one or more of SP, CNT and graphene; the protective layer comprises a first layer and a second layer, the first layer is coated on the first surface of the aluminum foil layer, and the second layer is coated on the second surface of the aluminum foil layer; the first layer and the second layer are made of the same or different materials; according to the composite current collector, the aluminum foil layer and the conductive polymer layer (such as PET, PP and PE) are compounded to form a novel composite current collector, so that the risk of short circuit caused by direct contact between negative electrode graphite and the aluminum foil is remarkably reduced by the structure under the condition that a battery cell is damaged; meanwhile, the invention further relates to a preparation method of the battery cell comprising the composite current collector, and the performance of the battery cell is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular relates to a composite current collector and a method for preparing a battery cell containing the composite current collector. Background Art

[0002] The current collector plays a vital role in lithium-ion batteries. Its main function is to conduct electricity and connect the positive and negative electrode materials of the battery to ensure the effective flow of current. With the rapid development of electronic products and the continuous improvement of battery energy density and charge and discharge rate, the performance requirements of the current collector are becoming increasingly stringent. However, although traditional aluminum foil has low cost and good conductivity as a battery current collector, there are still many safety hazards in its application process, especially when the battery cell is damaged by external force, which can easily lead to catastrophic consequences. Therefore, it is of great significance to improve the current collector and improve its safety and reliability.

[0003] In the prior art, when a battery cell is damaged by external forces, the positive and negative pole pieces may come into direct contact, causing a short circuit, which in turn leads to safety issues such as thermal runaway. Usually, battery damage may cause four different short circuits, including a short circuit between graphite and positive electrode materials, a short circuit between graphite and positive electrode aluminum foil, a short circuit between copper foil and aluminum foil, and a short circuit between positive electrode materials and negative electrode copper foil. Among them, direct contact between negative electrode graphite and aluminum foil is the main cause of thermal runaway. The current collector structure in the prior art lacks effective protection for aluminum foil, and fails to effectively prevent direct contact between negative electrode graphite and aluminum foil when the battery cell is damaged by external forces, resulting in a significant increase in safety risks.

[0004] Based on this, it is urgent to improve the existing preparation methods of current collectors and battery cells to solve the above-mentioned technical defects. Summary of the invention

[0005] One of the purposes of the present invention is to provide a composite current collector that can alleviate the short circuit of a battery cell under the action of external force in order to address the deficiencies of the prior art.

[0006] In order to achieve the above technical objectives, this application implements the following technical solutions:

[0007] A composite current collector comprises an aluminum foil layer and protective layers arranged on both sides of the aluminum foil layer in a thickness direction;

[0008] The protective layer includes a polymer material, a metal oxide and a conductive agent, wherein the conductive agent is one or more of SP, CNT, graphene and Ketjen black;

[0009] The protective layer comprises a first layer and a second layer, wherein the first layer is coated on the first surface of the aluminum foil layer, and the second layer is coated on the second surface of the aluminum foil layer;

[0010] The first layer and the second layer may be made of the same or different materials.

[0011] The above technical solution produces the following technical effects:

[0012] This patent proposes an innovative technical solution for a composite current collector, which aims to solve the short-circuit risk problem in the prior art. By compounding an aluminum foil layer with a conductive polymer layer (such as PET, PP, PE) to form a composite current collector, the possibility of a short circuit caused by direct contact between the negative electrode graphite and the aluminum foil is significantly reduced when the battery cell is damaged. The formation of this composite current collector not only ensures the safety of the battery when it is exposed to external hazards, but also avoids the risk of aluminum foil exposure due to deformation of the battery cell and shrinkage of the coating. At the same time, by introducing conductive agents (such as SP, CNT, graphene, etc.) and metal oxides (such as aluminum oxide, titanium oxide, etc.), while improving the conductivity, the rigidity of the material is enhanced, further improving the overall performance and safety of the battery.

[0013] As a further improvement to the composite current collector of the present invention, the polymer of the protective layer is any one of polyethylene terephthalate, polypropylene and polyethylene.

[0014] As a further improvement to a composite current collector of the present invention, the metal oxide includes one or more of boehmite, aluminum oxide, titanium oxide and magnesium oxide.

[0015] As a further improvement to the composite current collector of the present invention, the mass ratio of the polymer material, the metal oxide and the conductive agent is 80:10:10.

[0016] As a further improvement of a composite current collector of the present invention, at least one groove is provided through the first surface and the first layer arranged on the first surface by laser cleaning, and the groove includes a first through hole provided through the first layer and a first countersunk hole provided on the first surface.

[0017] As a further improvement of a composite current collector of the present invention, at least one groove is provided through the second surface and the second layer arranged on the second surface by laser cleaning, and the groove includes a second through hole provided through the second layer and a second countersunk hole provided on the second surface.

[0018] As a further improvement to the composite current collector of the present invention, the thickness of the protective layer is A, and the value range of A is: 1um-5um.

[0019] As a further improvement to the composite current collector of the present invention, the thickness of the aluminum foil layer is B, and the value range of B is 5um-8um.

[0020] One of the purposes of the present invention is to provide a method for preparing a battery cell which can alleviate the short circuit of the battery cell under the action of external force in order to address the deficiencies of the prior art.

[0021] In order to achieve the above technical objectives, this application implements the following technical solutions:

[0022] A method for preparing a battery cell comprising any of the above-mentioned composite current collectors comprises the following steps:

[0023] S101, mixing a polymer material, a metal oxide and a conductive agent, kneading and melting the mixed material through a screw extruder, and casting to prepare a protective layer;

[0024] S201, treating the aluminum foil by a corona process to prepare an aluminum foil layer, laminating the treated aluminum foil to form a composite current collector by laminating the protective layer prepared in step S101 on the aluminum foil layer;

[0025] S301, coating the active material on the surface of the composite current collector and drying it at a temperature of 80-120° C. to form the composite current collector;

[0026] S401, rolling, slitting, and sheeting the electrode sheet prepared in step S301, and then winding it with a separator to prepare a battery cell.

[0027] The above technical solution produces the following technical effects:

[0028] The battery cell preparation method of the present invention ensures the stability of the composite current collector and the reliability of the battery cell through a specific process flow. In step S101, a uniform protective layer with excellent conductive properties can be obtained by accurately controlling the mixing ratio and the conditions of mixing and melting. In step S201, the power of the corona process and the temperature control of the lamination process further ensure the bonding strength of the composite current collector and the performance of the battery cell. In step S301, the coating and drying of the active material, as well as the winding preparation of the battery cell in step S401, are all carried out under strictly controlled conditions to ensure the uniformity and consistency of the battery cell. Finally, the battery cell preparation method provided by the present invention not only improves the safety of the battery, but also optimizes the charge and discharge performance of the battery and prolongs the service life of the battery.

[0029] As a further improvement to the battery cell preparation method of the present application, the power of the corona process is controlled between 2KW and 10KW;

[0030] The ambient temperature during the lamination process was controlled between 100-200°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0032] Figure 1One of the schematic diagrams of the structure of the composite current collector in the present invention;

[0033] Figure 2 The second schematic diagram of the structure of the composite current collector in the present invention;

[0034] Figure 3 The third schematic diagram of the structure of the composite current collector in the present invention;

[0035] in:

[0036] 1-aluminum foil layer;

[0037] 11- First side;

[0038] 12- Second side;

[0039] 2- Protective layer;

[0040] 21-First floor;

[0041] 22- Second floor;

[0042] 3- Groove;

[0043] 31-first through hole;

[0044] 32-first countersunk hole;

[0045] 33- second through hole;

[0046] 34-Second countersunk hole. DETAILED DESCRIPTION

[0047] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by technicians in the technical field of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application.

[0048] In the description of the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected" and "fixed" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0049] Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the claims. Any technical personnel in this field may make several possible changes and modifications without departing from the concept of the present application. Therefore, the scope of protection of the present application shall be based on the scope defined by the claims of the present application.

[0050] It is known that when the battery cell is under the destruction of external force, the battery cell is damaged, and the positive and negative pole pieces are in direct contact, resulting in a short circuit, which is very likely to cause thermal runaway. There are four main short circuit modes caused by the contact between the positive and negative electrodes, namely, the contact between graphite and the positive electrode material, the contact between graphite and the positive electrode aluminum foil, the contact between copper foil and aluminum foil, and the contact between the positive electrode material and the negative electrode copper foil. Among them, the short circuit caused by the direct contact between the negative electrode graphite material and the aluminum foil is the main factor leading to thermal runaway. The core purpose of the present application is to provide a composite current collector, so that the battery cell can avoid the most serious short circuit caused by the direct contact between the negative electrode graphite and the aluminum foil when it is damaged by the outside world, thereby increasing the safety of the battery cell.

[0051] Specifically, in order to solve the above-mentioned technical defects, the composite current collector designed in the present application includes an aluminum foil layer 1 and a protective layer 2 arranged on both sides of the aluminum foil layer 1 in the thickness direction (Y-axis direction); the protective layer 2 includes a polymer material, a metal oxide and a conductive agent, and the conductive agent is one or more of SP, CNT, graphene, and Ketjen black; the protective layer 2 includes a first layer 21 and a second layer 22, the first layer 21 is coated on the first surface 11 of the aluminum foil layer 1, and the second layer 22 is coated on the second surface 12 of the aluminum foil layer 1; in addition, the materials of the first layer 21 and the second layer 22 are the same or different.

[0052] Among them, the principle of the above technical solution to avoid thermal runaway caused by direct contact between the negative electrode graphite material and the aluminum foil when the battery cell is damaged, resulting in excessive heat generation of the battery, is that when the battery cell is damaged by external force, the protective layer 2 in the composite current collector can provide additional physical isolation to reduce the direct contact between the negative electrode graphite and the aluminum foil layer 1. Due to the presence of the protective layer 2, the risk of short circuit between the positive and negative electrode materials is greatly reduced even when the battery cell is damaged. In addition, the material selection of the protective layer 2 further enhances the mechanical strength and electrochemical stability of the composite current collector, thereby improving the overall safety and reliability of the battery cell. In this way, the composite current collector can not only effectively alleviate the problem of battery cell short circuit caused by external force, but also improve the charging and discharging efficiency and cycle life of the battery.

[0053] The aluminum foil layer 1, as the basic part of the current collector, provides good conductivity and mechanical strength. It plays a key role in collecting and conducting current in the battery. At the same time, due to its light weight and high conductivity, it helps to improve the overall energy density of the battery, and ensures that the battery can efficiently conduct current during the charging and discharging process, providing a stable electrical connection. The protective layer 2 is composed of a polymer material, a metal oxide and a conductive agent, wherein the polymer material can provide flexibility and adhesion to the protective layer 2, which helps to resist mechanical stress and protect the aluminum foil layer 1. Metal oxides Metal oxides are insulating materials, and their conductivity cannot be improved after being added. The presence of metal oxides mainly improves the stability and rigidity of the protective layer. Conductive agents greatly improve the conductivity and improve the distribution and transmission efficiency of current.

[0054] It is worth noting that in the design of the first layer 21 and the second layer 22 in the present application, the first layer 21 is coated on the first side 11 of the aluminum foil layer 1 to provide good contact with the positive electrode active material. The second layer 22 is coated on the second side 12 of the aluminum foil layer 1 to provide good contact with the negative electrode material. This design ensures that the two polar materials can fully contact each other, thereby improving the overall electrochemical performance of the battery. Through the design of the first layer 21 and the second layer 22, the effective contact area between the electrode and the current collector is increased, thereby improving the efficiency of the battery. In addition, the materials of the first layer 21 and the second layer 22 are the same or different, considering that the technical solution of the present application can select the most suitable material for the different electrochemical environments of the positive and negative electrodes to improve the performance of the battery.

[0055] Furthermore, the polymer of the protective layer 2 is any one of polyethylene terephthalate, polypropylene and polyethylene. Among them, polyethylene terephthalate (PET) has high strength and rigidity, and can provide excellent structural support during the operation of the battery. In addition, polyethylene terephthalate (PET) can also withstand the operating temperature of the battery under high energy density conditions, reducing the risk of thermal runaway. At the same time, it has good corrosion resistance to electrolytes and other chemicals, which can extend the service life of the battery. Furthermore, by using PET, the protective layer 2 can improve the mechanical stability and durability of the battery and reduce the risk of damage.

[0056] However, the material of polypropylene (PP) is lightweight, which helps to reduce the overall weight of the battery and increase the energy density. Although as part of the protective layer 2, PP itself has good insulation properties and can prevent unnecessary short circuits. As a result, it is stable to common battery chemicals and effectively protects the aluminum foil from corrosion. Polyethylene (PE) has good flexibility and impact resistance, can adapt to the expansion and contraction during the operation of the battery, and has strong adaptability to electrolytes, avoiding performance degradation caused by chemical corrosion. During the manufacturing process, polyethylene (PE) is easy to process and form complex shapes, which is convenient for the production of large battery components.

[0057] As a further improvement of a composite current collector of the present invention, the metal oxide includes one or more of boehmite, aluminum oxide, titanium oxide and magnesium oxide. It is worth noting that the conductivity of oxides is generally poor. After adding, the internal resistance will increase and the conductivity of the battery cell will decrease. Therefore, a certain amount of conductive agents such as SP, CNT, etc. mentioned above need to be added to this layer.

[0058] Furthermore, Boron Nitride has a certain thermal conductivity, which helps to improve the effective heat dissipation of the composite current collector under high temperature working conditions. At the same time, the material shows good durability in battery environments (such as electrolytes, etc.), reducing the risk of performance degradation of the battery in long-term use. Magnesium oxide has good high-temperature stability, is suitable for high-power operating conditions, and is not easy to degrade. In addition, magnesium oxide can improve the toughness of the current collector and prevent brittle fracture under extreme conditions.

[0059] Furthermore, the mass ratio of polymer material, metal oxide and conductive agent is 80:10:10. Thus, as the basic component of the composite current collector, the polymer material provides the necessary mechanical strength, flexibility and chemical resistance. A large proportion of polymer material helps to ensure that the current collector maintains stable physical properties under battery operating conditions. The high proportion of polymer enables the current collector to effectively resist rupture or cracking when subjected to physical stress. An appropriate amount of metal oxide can enhance the conductivity and thermal management properties of the composite current collector. Although the proportion is relatively low, they play an important role in improving performance.

[0060] It is worth noting that, considering that the current mainstream composite current collector has a PET layer in the middle and metal layers on both sides, it is relatively difficult to weld the tabs and the internal resistance is large. However, the present application has a metal layer in the middle and a protective layer 2 on both sides. The slots for welding the tabs can be easily washed out by laser cleaning. The slots can be cleaned before or after coating, and the internal resistance is small after welding. Figure 2As shown, the first surface 11 of the composite current collector in the present invention and the first layer 21 arranged on the first surface 11 are penetrated by laser cleaning to form at least one groove 3, and the groove 3 includes a first through hole 31 penetrating the first layer 21 and a first countersunk hole 21 arranged on the first surface 11. Among them, the through hole position is set at the alignment position of the negative electrode ear, thereby reducing the thickness of the finished battery cell and increasing the energy density of the battery cell. The groove 3 includes the first through hole 31 penetrating the first layer 21 and the first countersunk hole 21 arranged on the first surface 11, which can increase the surface area of ​​the material to enhance the contact between the electrode and the current collector, and can effectively improve the energy density and power density of the battery. Thus, the technical defect that the groove 3 is designed in the protective layer 2 without involving the aluminum foil layer 1 in the prior art is solved, thereby causing the expansion of the gas generated by the electrochemical reaction during the charging and discharging process of the battery, which may cause poor contact between the electrode and the current collector, thereby affecting the battery performance.

[0061] In addition, Figure 3 As shown, the second surface 12 and the second layer 22 arranged on the second surface 12 are penetrated by at least one groove 3 by laser cleaning, and the groove 3 includes a second through hole 33 penetrating the second layer 22 and a second countersunk hole 34 arranged on the second surface 12. Among them, the first surface 11 and the second surface 12 are connected to electrodes or pole ears of different polarities. In the specific implementation process, the setting of the first groove 3 and the second groove 3 respectively produces two different composite current collectors, thereby providing a more stable and uniform current distribution during the battery charging and discharging process. The design of the groove 3 of the second surface 12 is also achieved by laser cleaning technology, which ensures the bonding strength between the second layer 22 and the second surface 12, while increasing the contact area between the electrode and the current collector, further improving the charging and discharging efficiency and cycle life of the battery. Through this design, the battery can maintain good electrochemical properties during high-rate charging and discharging, and reduce local overheating and battery performance degradation caused by uneven current density.

[0062] Specifically, the thickness value of the protective layer 2 is A, and the value range of A is: 1um-5um. In the specific implementation process, the value of A can be 1um, 1.5um, 2um, 2.5um, 3um, 3.5um, 4um, 4.5um or 5um. The thickness of the protective layer 2 has a direct impact on the performance of the battery. Too thin may lead to uneven current distribution, while too thick may increase the internal resistance of the battery and affect the charging and discharging efficiency. Therefore, it is crucial to choose a suitable thickness of the protective layer 2. In practical applications, according to the use requirements and performance indicators of the battery, the thickness of the protective layer 2 can be flexibly adjusted to achieve the best electrochemical performance. In addition, the material selection of the protective layer 2 also needs to consider factors such as its conductivity, chemical stability, and compatibility with electrode materials to ensure the overall stability and reliability of the battery.

[0063] As a further improvement to a composite current collector of the present invention, the thickness value of the aluminum foil layer 1 is B, and the value range of B is: 5um-8um. In the specific implementation process, the value of B can be 5um, 5.5um, 6um, 6.5um, 7um, 7.5um or 8um. As the supporting structure of the current collector, the thickness of the aluminum foil layer 1 also has an important influence on the mechanical strength and safety of the battery. Although a thinner aluminum foil layer 1 can reduce the weight of the battery, it may reduce the mechanical strength of the battery, while a thicker aluminum foil layer 1 can increase the mechanical strength, but will increase the weight and cost of the battery. Therefore, selecting a suitable thickness of the aluminum foil layer 1 can take into account the weight and cost of the battery while ensuring the battery performance. In practical applications, the thickness of the aluminum foil layer 1 needs to be optimized according to the use environment and performance requirements of the battery to achieve the best overall performance.

[0064] Furthermore, in order to further improve the safety of the battery cell, the present application also designs a method for preparing a battery cell comprising any of the above-mentioned composite current collectors, specifically comprising the following steps:

[0065] S101, preparing a protective layer 2 by mixing a polymer material, a metal oxide and a conductive agent, kneading and melting the mixed material through a screw extruder, and casting;

[0066] S201, treating the aluminum foil by a corona process to prepare an aluminum foil layer 1, laminating the treated aluminum foil to laminate the protective layer 2 prepared in step S101 to the aluminum foil layer 1 to form a composite current collector;

[0067] S301, coating the active material on the surface of the composite current collector and drying it at a temperature of 80-120° C. to form the composite current collector;

[0068] S401, rolling, slitting, and sheeting the anode sheet prepared in step S301, and then winding it with a separator to prepare a battery cell.

[0069] Through the above technical solution, the aluminum foil is treated with a corona process in step S201 to make its surface more active, and then the prepared protective layer 2 is laminated to the treated aluminum foil layer 1. The corona treatment improves the surface energy of the aluminum foil, enhances the adhesion between the protective layer 2 and the aluminum foil, and reduces the risk of delamination or peeling. In addition, on the one hand, the corona process can remove organic matter on the surface of the aluminum foil layer 1, making the surface cleaner; on the other hand, through the physical etching method of corona, the surface of the aluminum foil layer 1 becomes rougher, further effectively improving the bonding force between the protective layer 2 and the aluminum foil layer 1, making it difficult to detach.

[0070] Furthermore, the active material is spread on the surface of the composite current collector and dried at a temperature of 80-120°C to form. In the specific implementation process, the active material of the present application is a positive electrode active slurry (comprising 97.6wt% LiCoO2, 0.8wt%, 0.7wt% SP and 0.7wt% CNT) to prepare a positive electrode sheet. In addition, under controlled temperature conditions, it can ensure that the positive electrode slurry is evenly coated while avoiding material degradation due to excessive temperature. A good coating effect can improve the contact between the electrode and the electrolyte and increase the energy density of the battery.

[0071] Furthermore, the power of the corona process is controlled between 2KW-10KW; the ambient temperature during the lamination process is controlled between 100-200°C.

[0072] The power of the corona process is controlled between 2KW-10KW, which can ensure that the surface of the aluminum foil is properly treated. The surface activity will not be affected by too low power, nor will the material be damaged by too high power. By precisely controlling the corona power, the surface of the aluminum foil can be uniformly treated, thereby ensuring good bonding between the protective layer 2 of the composite current collector and the aluminum foil layer 1. The ambient temperature during the lamination process is controlled between 100℃-200℃ to ensure that the protective layer 2 and the aluminum foil layer 1 can be fully integrated during the lamination process, while avoiding degradation of material properties due to excessively high temperature. Appropriate lamination temperature helps to form a stable structure.

[0073] The present invention is further described in detail below in conjunction with specific embodiments, but the embodiments of the present invention are not limited thereto. At the same time, the present application performs acupuncture tests and battery rate performance tests on Examples 1-20 and Comparative Examples 1-3. Specifically, the process of the acupuncture test is: take 10 cells each from the comparative example and the embodiment, charge them to 4.5V at a constant current of 0.5C, and then charge them to 0.02C at a constant voltage. Then, the fully charged cell is punctured at 25±2°C using a tungsten steel needle with a diameter of 4mm, a taper of 15°, and a total length of 100mm in the middle of the cell, so that the steel needle passes through the cell, and the cell is considered to have passed if it does not catch fire or explode. Among them, the method of testing the battery rate performance is to take 3 cells each from Comparative Examples 1-3 and Examples 1-20, charge them to 4.5V at a constant current of 0.5C, and then discharge them to 3V at 1.5C for testing.

[0074] Example 1

[0075] The protective layer 2 of the composite current collector in this embodiment has a thickness of 1 μm and is prepared by fully mixing PET, Al2O3 and SP in a mass ratio of 80:10:10, then mixing and melting through a screw extruder, and casting;

[0076] The aluminum foil layer 1 has a thickness of 6 μm and is prepared by treating the aluminum foil in a corona manner; the protective layer 2 is laminated on both sides of the aluminum foil layer 1 at 150° C. to form a composite current collector.

[0077] The active slurry of the positive electrode sheet is 97.6wt% LiCoO2, 0.7wt% SP and 0.7wt% CNT, which is coated on the surface of the above-mentioned composite current collector, dried at 100°C and formed, and then rolled, slit, and sheeted, and then wound with the separator and the negative electrode sheet into a bare battery cell, which is then packaged, baked, injected, formed, and sealed again to prepare the battery cell.

[0078] Example 2

[0079] The difference from Example 1 is that the conductive agent of the protective layer 2 is 10% by mass of CNT. The rest is as described in Example 1 and will not be repeated here.

[0080] Example 3

[0081] The difference from Example 1 is that the conductive agent of the protective layer 2 is 10% by mass of graphene, and the rest is as described in Example 1 and will not be repeated here.

[0082] Example 4

[0083] The difference from Example 1 is that the conductive agent of the protective layer 2 is 10% by mass of Ketjen black, and the rest is as described in Example 1 and will not be repeated here.

[0084] Example 5

[0085] The difference from Example 1 is that the conductive agent of the protective layer 2 is a mixture of 5 mass % SP and 5 mass % CNT, and the rest is as described in Example 1 and will not be repeated here.

[0086] Example 6

[0087] The difference from Example 1 is that the conductive agent of the protective layer 2 is a mixture of 5 mass % SP and 5 mass % Ketjen black, and the rest is as described in Example 1 and will not be repeated here.

[0088] Example 7

[0089] The difference from Example 1 is that the conductive agent of the protective layer 2 is a mixture of 5 mass % SP and 5 mass % graphene, and the rest is as described in Example 1 and will not be repeated here.

[0090] Example 8

[0091] The difference from Example 1 is that the conductive agent of the protective layer 2 is a mixture of 5% by mass of CNT and 5% by mass of Ketjen black. The rest is as described in Example 1 and will not be repeated here.

[0092] Example 9

[0093] The difference from Example 1 is that the conductive agent of the protective layer 2 is a mixture of 5% by mass of CNT and 5% by mass of graphene. The rest is as described in Example 1 and will not be repeated here.

[0094] Example 10

[0095] The difference from Example 1 is that the conductive agent of the protective layer 2 is a mixture of 5% by mass of Ketjen black and 5% by mass of graphene. The rest is as described in Example 1 and will not be repeated here.

[0096] Embodiment 11

[0097] Different from Example 1, the conductive agent of the protective layer 2 is a mixture of 3.3% by mass of CNT, 3.3% by mass of Ketjen black and 3.3% by mass of graphene (the mass fraction of the conductive agent after blending is selected to be approximately 10%), and the rest is as described in Example 1 and will not be repeated here.

[0098] Example 12

[0099] Different from Example 1, the conductive agent of the protective layer 2 is a mixture of 3.3% by mass of SP, 3.3% by mass of Ketjen black and 3.3% by mass of graphene (the mass fraction of the conductive agent after blending is selected to be approximately 10%), and the rest is as described in Example 1 and will not be repeated here.

[0100] Embodiment 13

[0101] Different from Example 1, the conductive agent of the protective layer 2 is a mixture of 3.3% by mass of SP, 3.3% by mass of CNT and 3.3% by mass of graphene (the mass fraction of the conductive agent after blending is selected to be approximately 10%), and the rest is as described in Example 1 and will not be repeated here.

[0102] Embodiment 14

[0103] The difference from Example 1 is that the metal oxide of the protective layer 2 is boehmite, and the rest is as described in Example 1 and will not be repeated here.

[0104] Embodiment 15

[0105] The difference from Example 1 is that the metal oxide of the protective layer 2 is TiO2, and the rest is as described in Example 1 and will not be repeated here.

[0106] Example 16

[0107] The difference from Example 1 is that the metal oxide of the protective layer 2 is MgO, and the rest is as described in Example 1 and will not be repeated here.

[0108] Embodiment 17

[0109] The difference from Example 1 is that the thickness of the protective layer 2 is changed to 2 um, and the rest is as described in Example 1 and will not be repeated here.

[0110] Embodiment 18

[0111] The difference from Example 1 is that the thickness of the protective layer 2 is changed to 3 um, and the rest is as described in Example 1 and will not be repeated here.

[0112] Embodiment 19

[0113] The difference from Example 1 is that the thickness of the protective layer 2 is changed to 4 um, and the rest is as described in Example 1 and will not be repeated here.

[0114] Embodiment 20

[0115] The difference from Example 1 is that the thickness of the protective layer 2 is changed to 5 um, and the rest is as described in Example 1 and will not be repeated here.

[0116] Comparative Example 1

[0117] The difference from Example 1 is that there is no protective layer 2 on the surface of the aluminum foil layer 1, and the thickness of the aluminum foil layer 1 is 6 um. The rest is as described in Example 1 and will not be repeated here.

[0118] Comparative Example 2

[0119] The difference from Example 1 is that the protective layer 2 does not contain metal oxide, the mass percentage of PET is increased to 90%, and the rest is as described in Example 1 and will not be repeated here.

[0120] Comparative Example 3

[0121] The difference from Example 1 is that the mass percentage of the conductive agent SP in the conductive PET layer is reduced to 0.5%, and the mass percentage of PET is increased to 89.5%. Other details are as described in Example 1 and will not be repeated here.

[0122] The results of the acupuncture tests of Examples 1-20 and Comparative Examples 1-3 are shown in Table 1 below:

[0123]

[0124]

[0125] Table 1

[0126] According to Table 1, compared with Comparative Example 1, the safety of the battery cell made of the composite current collector of the present application is significantly improved. The reason is that during acupuncture, the protective layer 2 has better protection for the aluminum foil layer 1, avoiding direct contact between the aluminum foil and the graphite, resulting in thermal runaway and battery cell failure. From Table 1, it can be found that the battery cell acupuncture pass rate of the composite current collector of the protective layer 2 mixed with different metal oxides is equivalent, while the safety of the group without adding metal oxides is relatively poor. This is because after adding metal oxides, the protective layer 2 shrinks less under the heat state during the acupuncture process, which can avoid short circuit between the aluminum foil and the negative electrode to a greater extent, thereby improving the safety of the battery. From Table 1, it can also be found that when a single-component conductive agent is mixed into the protective layer 2, the safety is relatively good, and the relative deviation of multiple components may be related to the relatively poor conductive network formed by the single-component conductive agent. When the conductive network is relatively poor, the short-circuit current is relatively small, the heat generation of the battery cell is small, the shrinkage degree of the protective layer 2 becomes smaller, and the direct contact area between the aluminum foil and the graphite is reduced, thereby improving the overall safety of the battery cell. From the perspective of the thickness of the protective layer 2, when the thickness of the protective layer 2 becomes thicker, its overall safety is improved, which means that when the thickness of the PET layer increases, its anti-destruction ability becomes stronger and the protection of the aluminum foil increases.

[0127] The results of the battery rate performance tests of Examples 1-20 and Comparative Examples 1-3 are shown in Table 2 below:

[0128]

[0129] Table 2

[0130] According to the data in Table 2, it is obvious that compared with Comparative Examples 1-3, the rate performance of the battery cell introduced with the composite current collector in the present application will decrease, because the internal resistance of the composite current collector itself is larger than that of the ordinary current collector. It can be found in the composite current collector battery cell group that when a single-component conductive agent is added, the rate performance of the battery cell is worse than when two or three conductive agents are added together. This is because a single-component conductive agent is more difficult to form a long-range conductive network, and when multiple conductive agents are added together, due to the combination of points and lines or points and surfaces or lines and surfaces, a better conductive network can be formed, which improves the conductivity of the current collector, thereby improving the overall rate performance of the battery cell; it can also be seen from the table that when different metal oxides are mixed in the composite current collector, the rate performance of the battery cell is not much different, and the rate of the battery cell is more related to the conductive network formed by the conductive agent, and has little correlation with the type of inorganic metal oxide.

[0131] The above are only preferred embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A composite current collector, characterized in that: It comprises an aluminum foil layer (1) and protective layers (2) arranged on both sides of the aluminum foil layer (1) in the thickness direction; The protective layer (2) comprises a polymer material, a metal oxide and a conductive agent, wherein the conductive agent is one or more of SP, CNT, graphene and Ketjen black; The protective layer (2) comprises a first layer (21) and a second layer (22), wherein the first layer (21) is coated on the first surface (11) of the aluminum foil layer (1), and the second layer (22) is coated on the second surface (12) of the aluminum foil layer (1); The first layer (21) and the second layer (22) are made of the same or different materials.

2. A composite current collector according to claim 1, characterized in that: The polymer of the protective layer (2) is any one of polyethylene terephthalate, polypropylene and polyethylene.

3. A composite current collector according to claim 1, characterized in that: The metal oxide includes one or more of boehmite, aluminum oxide, titanium oxide and magnesium oxide.

4. A composite current collector according to claim 1, characterized in that: The mass ratio of the polymer material, the metal oxide and the conductive agent is 80:10:

10.

5. A composite current collector according to claim 1, characterized in that: At least one groove (3) is formed through the first surface (11) and the first layer (21) arranged on the first surface (11) by laser cleaning, and the groove (3) comprises a first through hole (31) extending through the first layer (21) and a first countersunk hole (32) arranged on the first surface (11).

6. A composite current collector according to claim 1, characterized in that: At least one groove (3) is formed through the second surface (12) and the second layer (22) arranged on the second surface (12) by laser cleaning, and the groove (3) comprises a second through hole (33) extending through the second layer (22) and a second countersunk hole (34) arranged on the second surface (12).

7. A composite current collector according to claim 1, characterized in that: The thickness of the protective layer (2) is A, and the value range of A is: 1um-5um.

8. The composite current collector according to claim 1, characterized in that: The thickness value of the aluminum foil layer (1) is B, and the value range of B is: 5um-8um.

9. A method for preparing a battery cell comprising the composite current collector according to any one of claims 1 to 8, characterized in that: The steps include: S101, preparing a protective layer (2) by mixing a polymer material, a metal oxide and a conductive agent, kneading and melting the mixed materials through a screw extruder, and casting; S201, treating the aluminum foil by a corona process to prepare an aluminum foil layer (1), laminating the treated aluminum foil by laminating the protective layer prepared in step S101 onto the aluminum foil layer (1) to form a composite current collector; S301, coating the active material on the surface of the composite current collector and drying it at a temperature of 80-120° C. to form the composite current collector; S401, rolling, slitting, and sheeting the electrode sheet prepared in step S301, and then winding it with a separator to prepare a battery cell.

10. The method for preparing a battery cell according to claim 9, characterized in that: The power of the corona process is controlled between 2KW and 10KW; The ambient temperature during the lamination process is controlled between 100-200°C.

Citation Information

Patent Citations

  • Composite current collector tab as well as preparation method and application thereof

    CN116826066A

  • Current collector and preparation method thereof, battery pole piece and battery

    CN117199381A

  • Composite current collector and manufacturing method thereof, electrode plate, secondary battery and electric device

    CN118511290A

  • Pole piece and lithium ion battery

    WO2023093576A1

  • Composite current collector and manufacturing method therefor, electrode sheet, secondary battery and electric apparatus

    WO2024060176A1